Integrating the automated car manufacturing system based on RFID and analysis using modules. Issue 3 (August 2020) - Rahul, R.; Kumaraswamy, A.
Abstract: In this module the analysis of the automated car manufacturing system is done. RFID tag is used to read each section of automobile manufacturing. There is an IR sensor in each segment of work envelops to detect the job completion. The first segment is for engine front and rear suspension module of the car, the second one is to integrate the Chassis Marriage Module, the third for integrating the Trim line of a car, and the fourth for implementing the Final line and testing the Quality of the Car. Here the RFID tag reads and stores the information detected by IR sensor. The Arduino controller connected to the IR sensor sends the data wirelessly to the MATLAB software through ZigBee module. This makes the production work simpler and effective. Also the throughput can be checked and analysed. Thus the performance and efficiency of manufacturing process can be analysed. Also the failure performance at distinct levels can be calculated. This will certainly help in analysing the working condition of each work envelope at regular intervals.